EXCISE TAX AND ITS ROLE IN FORMING STATE BUDGET REVENUES (International Conference on Modern Science and Scientific Studies, 2025)
This thesis also specifically addresses the current status of excise goods in the Republic of Uzbekistan and the share of excise tax in state budget revenues, as well as the role and importance of excise tax in the tax system of the Republic of Uzbekistan.